1973
DOI: 10.1037/h0033978
|View full text |Cite
|
Sign up to set email alerts
|

A locus of control scale for children.

Abstract: The relationships between locus of control and other personality variables were studied, using the Nowicki-Strickland Scale. The broad hypotheses were that internal locus of control would be related to a number of other competence-type behaviors and adaptive social functioning. Results of various studies are presented, and it is concluded that the Nowicki-Strickland Locus of Control Scale appears to offer an objective, relatively precise, quick method for assessing a generalized belief in locus of control and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
617
1
22

Year Published

1989
1989
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 1,318 publications
(657 citation statements)
references
References 17 publications
17
617
1
22
Order By: Relevance
“…[3][4][5][6][7][8] This study was inspired by a previous report that concluded that LOC information might be useful to enhance patient compliance in orthodontic treatment. 9 Although a specific LOC questionnaire for orthodontic patients 9 is available, there were 3 reasons for selecting the RICS and the NSECS in this study: (1) the RICS and the NSEC have already been used many times in their translated forms with proven reliability and validity for the general population and orthodontic patients 15,16,[23][24][25][26] ; (2) a minimum elementary level of education is required for use; and (3) these tests are practical for use in clinical practice with free distribution and rapid completion, and most patients can complete them in 15 minutes. The initial alternative hypothesis of this study stated that patient compliance is related to the patient's LOC and thus could be predicted by an LOC survey before treatment.…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5][6][7][8] This study was inspired by a previous report that concluded that LOC information might be useful to enhance patient compliance in orthodontic treatment. 9 Although a specific LOC questionnaire for orthodontic patients 9 is available, there were 3 reasons for selecting the RICS and the NSECS in this study: (1) the RICS and the NSEC have already been used many times in their translated forms with proven reliability and validity for the general population and orthodontic patients 15,16,[23][24][25][26] ; (2) a minimum elementary level of education is required for use; and (3) these tests are practical for use in clinical practice with free distribution and rapid completion, and most patients can complete them in 15 minutes. The initial alternative hypothesis of this study stated that patient compliance is related to the patient's LOC and thus could be predicted by an LOC survey before treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Within this study, scoring was reversed to achieve consistency with the positive direction of scores for other moderator variables. High reliability and validity levels of this measure have been reported in several studies (Nowicki & Strickland, 1973).…”
Section: Locus Of Control-thementioning
confidence: 99%
“…Nowicki-Strickland Locus of Control Scale (Nowicki & Strickland, 1973) was used to measure the extent to which children make external versus internal attributions. On this 40-item, two-choice measure, high scores are indicative of high externality.…”
Section: Locus Of Control-thementioning
confidence: 99%
See 1 more Smart Citation
“…''Adherence'' was then introduced and used interchangeably with compliance. 2 Adherence is defined as the extent to which a person's behavior, such as taking medication, following a diet, and/or executing lifestyle changes, corresponds with recommendations the person has agreed to with a healthcare provider. 3 It also implies that people freely choose to undertake behavioral plans, have input to them, and have collaborative involvement in developing and adjusting their treatment strategy.…”
Section: Introductionmentioning
confidence: 99%